2005
DOI: 10.3353/omp.10.131
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and Electron Microscopic Study of the Biodegradation Processes of Chitin and Chitosan Implanted in Rat Alveolar Bone

Abstract: histochemical and electron microscopic study of the biodegradation processes of chitin and chitosan implanted in rat alveolar bone. Oral Med Pathol 2005; 10: 131-138, ISSN 1342-0984 The present study was designed to investigate histochemically the biodegradation processes of chitin and chitosan implanted in rat alveolar bone. Lysozyme was immunohistochemically detected using postembedding immunogold labeling. The degradation process was ultrastructurally observed using the lectin-colloidal gold technique with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We previously reported an investigation of the biodegradation processes of chitosan fibers implanted in the bone tissue and found that it should be a suitable biomaterial for bone surgery and bone regenerative medicine [ 51 ]. It was suggested that chitosan -based materials bind to growth factors and release them in a controlled manner due to their cationic nature and predictable degradation rate.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported an investigation of the biodegradation processes of chitosan fibers implanted in the bone tissue and found that it should be a suitable biomaterial for bone surgery and bone regenerative medicine [ 51 ]. It was suggested that chitosan -based materials bind to growth factors and release them in a controlled manner due to their cationic nature and predictable degradation rate.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of deacetylation of chitosan, could also affect the biological character of chitosan, including biodegradation of chitosan caused by lysozyme enzyme produced by inflammatory cells and macrophages neutrophil. 7 Actually, chitosan is a source of the active N-acetyl-D-glucosamine dimer, therefore if it is applied to the wound area, it will make inflammatory cells release lysozyme. 3 Neutrophils produced by inflammatory cells, furthermore, will migrate into the wound area several hours after the injury and will reach a maximum concentration in about 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…9 Therefore, if chitosan containing the active N-acetyl-D-glucosamine dimer experiences biodegradation, it will form cross-linked with glycosaminoglycan and glycoprotein which plays a role in biological processes, including both the cell and matrix interactions and the activation of growth factors. 7 Growth factors, such as bone morphogenetic protein-2 (BMP-2) which is a superfamily of transforming growth factor b (TGF-b) then will stimulate the differentiation of osteoblastic-cell. 10 Thus, chitosan is able to accelerate wound healing process through fibrinogenic mediators, such as growth factors.…”
Section: Discussionmentioning
confidence: 99%